How can social responsibility enhance the green value of financial enterprises? Empirical research based on the qualitative comparative analysis method - Zhang, Zhe; Wang, Qingjin; Lu, Binbin (Frontiers in Environmental Science, 2022)
Given the high revenues of financial enterprises, they should carry out their social responsibilities to contribute to sustainable social and economic development. The purpose of this study is to provide a more efficient strategy for China’s listed financial enterprises to improve their green value under the condition of realizing the optimal allocation of their resources in the future. To this end, the present study adopts the fuzzy set qualitative comparative analysis method on 26 domestic listed banks to examine the impact of social responsibility undertaking on the improvement of the green values of enterprises. The findings show that the promotion of green values of listed financial enterprises in China does not simply depend on a one-dimension social responsibility investment but requires a combination of multiple dimensions. Accordingly, policy recommendations are provided to help ensure the long-term development of financial enterprises while achieving sustainable economic development.